SOCIAL MONITORING IN THE SCIENTIFIC RESEARCH ACTIVITY OF FUTURE SOCIAL WORKERS - Elena Zritneva (Вестник Северо-Кавказского федерального университета, 2022)
In article research activity in the university is considered as an important component of vocational training. The tendencies in the preparation of students studying in the field of training are marked. March 39.03.02 Social work (bachelor's level). Briefly characterized by research activities in the university. The importance and possibility of using social monitoring as a social technology in the research activities ofstudents is shown. The example of the Department of Social Technologies of the North Caucasus Federal University shows the organization of research activities of students. Attention is paid to the organization of monitoring ((Independent evaluation of the quality of services rendered by the social services centers of the population of the Stavropol Territory».